The stability of cannon position on tank prototype using PID controller - Dimas Farid Arief Putra; Ahmad Syahril Muharom (Institute of Advanced Engineering and Science, 2021)
Tank is a war vehicle made of steel that can be operated on various fields. With various fields and a large amount of terrain that the tank had to pass, this made it necessary for the tank to be able to stabilize the cannon so that the cannon be able to fire right on the target. This study discusses the stability of the position of the cannon on the tank prototype using the PID control system. PID values are obtained by using the Ziegler-Nichols tuning formula and simulink. The system using Arduino MEGA 2560 as microcontroller, gyroscope & accelerometer for the feedback sensor and cannon that driven using three servos that representing the x-axis, y-axis and z-axis. The highest average error value is 4.67 degrees with an overall average value of 2.29 degrees and an accuracy percentage of 98% when the tank tilted randomly on the x-axis, y-axis and z-axis.